Anticancer carbonic anhydrase inhibitors: a patent review (2008 – 2013). (June 2013) - Monti, Simona Maria; Supuran, Claudiu T; De Simone, Giuseppina
Abstract : Introduction: Human carbonic anhydrases (EC 4.2.1.1) IX (hCA IX) and XII (hCA XII) are two tumor-associated proteins, being overexpressed in many tumors and involved in critical processes associated with cancer progression and response to therapy. Both are multi-domain proteins consisting of an extracellular catalytic domain (CA), a transmembrane portion (TM) and an intracytoplasmic (IC) segment. These domains have peculiar biochemical and physiological features. CA IX contains an additional proteoglycan-like (PG) domain at the N-terminus which constitutes a unique feature of this enzyme within the CA family. Areas covered: Starting from a brief description of the main molecular and catalytic features of both enzymes, their role in tumor physiology and their three-dimensional structure, this review describes the main classes of small molecule inhibitors, investigated between 2008 and 2013, able to inhibit these enzymes for both diagnostic and therapeutic applications. Expert opinion: A consistent number of patents on molecules able to inhibit the catalytic activity of CA IX and CA XII have been recently reported. Most patents deal with classical sulfonamide derivatives, demonstrating that introducing suitable substituents on the inhibitor scaffold, good selectivity can be obtained. However, the most impressive results are related to compounds containing novel chemotypes, such as coumarins and thiocumarins. Thus, it is expected that research in next future will be more dedicated to the development of molecules containing new chemotypes and a large number of studies in such field have already been published demonstrating the role of these enzymes in carcinogenesis and metastases formation.